Additive manufacturing : fundamentals and advancements - Srivastava, Manu; Rathee, Sandeep; Maheshwari, Sachin; Kundra, T. K. (CRC Press/Taylor & Francis Group, 2019)
There is a growing need for manufacturing optimization all over the world. The immense market of Additive Manufacturing (AM) technologies dictates a need for a book that will provide knowledge of the various aspects of AM for anyone interested in learning about this fast-growing topic. This book disseminates knowledge of AM amongst scholars at graduate level, post graduate level, doctoral level, as well as industry personnel. The objective is to offer a state-of-the-art book which covers all aspects of AM and incorporates all information regarding trends, historical developments, classifications, materials, tooling, software issues, dynamic design, principles, limitations, and communication interfaces in a one-stop resource. Features: Breaks down systematic coverage of various aspects of AM within four distinct sections Contains details of various AM techniques based on ASTM guidelines Discusses many AM applications with suitable illustrations Includes recent trends in the field of AM Covers engineering materials utilized as raw materials in AM Compares AM techniques with different traditional manufacturing methods